Spatial variations in the zooplankton community from the Corumbá Reservoir, Goiás State, in distinct hydrological periods - DOI: 10.4025/actascibiolsci.v31i3.4132 - Takahashi, Erica Mayumi (2009)
This study evaluated the spatial variations in species richness and abundance of zooplankton over a hydrological cycle, and also verified the influence of physical and chemical water variables and chlorophyll-a concentrations on the abundance of these organisms. The tested hypothesis was that the zooplankton community presents higher species richness in lotic environments and higher abundance in lentic ones. One hundred forty species were identified, distributed among rotifers (88), testate amoebae (35), cladocerans (13) and copepods (4). Higher values of species richness and abundance were observed during the dry period. During both hydrological periods, the copepods presented high abundance values, due to the contribution of young stages, followed by rotifers, cladocerans and testate amoebae. In general, testate amoebae presented high values of species richness and abundance in lotic sampling stations, whereas the other zooplankton groups (rotifers, cladocerans and copepods) presented higher abundances in lentic environments and higher species richness in lotic ones. The Pearson correlation analysis evidenced the importance of physical and chemical water variables and food resource availability influencing the variation of organisms’ abundance.